THE RELATIONSHIP BETWEEN GLENOHUMERAL JOINT TOTAL ROTATIONAL RANGE OF MOTION AND THE FUNCTIONAL MOVEMENT SCREEN™ SHOULDER MOBILITY TEST - Sprague, Peter A. (Sports Physical Therapy Section, 2014)
PURPOSE/BACKGROUND: Side to side asymmetry in glenohumeral joint rotation correlates with injury risk in overhead athletes. The purpose of the current study was to identify the relationship between side‐to‐side asymmetries in glenohumeral joint total rotational range of motion and shoulder mobility test scores from the Functional Movement Screen™ in collegiate overhead athletes. The authors hypothesized that asymmetries of > 10° in glenohumeral total rotation would not be associated with asymmetrical findings in the Functional Movement Screen™ (FMS) shoulder mobility test. METHODS: Passive glenohumeral total rotational range of motion and the shoulder mobility test of the FMS were measured during pre‐participation examinations in 121 NCAA male and female Division II collegiate overhead athletes from varied sports. Passive shoulder range of motion was measured in supine at 90° of abduction, with the humerus in the scapular plane using two measurers and a bubble goniometer. A Pearson Chi‐square analysis, p<.05 was used to associate the presence of asymmetries in glenohumeral joint rotation and in the FMS shoulder mobility test in each subject. RESULTS: 40/114 (35.1%) athletes demonstrated asymmetries in total glenohumeral rotation. 45/114 (39.5%) athletes demonstrated asymmetries in the shoulder mobility test. Only 17 of the 45 subjects who demonstrated asymmetry on the shoulder mobility test also demonstrated glenohumeral joint rotation differences of > 10°. Athletes with asymmetries in rotation of > 10° were not any more likely to have asymmetries identified in the shoulder mobility test (95% CI=.555‐2.658, P=.627). CONCLUSIONS: Glenohumeral joint range of motion is one of multiple contributors to performance on the FMS shoulder mobility test, and alone, did not appear to influence results. The FMS shoulder mobility test should not be used alone as a means of identifying clinically meaningful differences of shoulder mobility in the overhead athlete. Clinicians working with overhead athletes may consider using both assessments as a complete screening tool for injury prevention measures. LEVEL OF EVIDENCE: Level 3